Konsep Pendidikan Islam Menurut Kyai Haji Abdul Wahid Hasyim - Dewi Wahyuto Sejati (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This article aims to explain the concept of modern Islamic education according to Kyai Haji Abdul Wahid Hasyim who is known as a pesantren reformer. This study uses library research methods. The results to be obtained in this study are the importance of Wahid Hasyim's ideas and thoughts in the world of Islamic boarding schools. He is the one who brings renewal in the pesantren. His goal is to make the students have prowess in the fields of religion, academics and skills. Islamic boarding schools are educational institutions capable of providing comprehensive knowledge. Religious knowledge, general knowledge of language and skills in all fields.